Estudo comparativo de desfechos de pacientes cirúrgicos diagnosticados com COVID-19 - Silva, Larissa Eduarda da; Gnatta, Juliana Rizzo; Lima, Camila; Poveda , Vanessa de Brito (Revista SOBECC, 2024)
Objective: To compare the outcomes of patients undergoing conventional gastrointestinal surgeries who developed COVID-19 to those who were not infected. Method: Descriptive comparative study. Data were collected from 142 medical records, during the period from March 2020 (beginning of the pandemic in Brazil) to December 2021. Study approved by the Research Ethics Committee (CAAE: 29473520.2.0000.5392). Results: The profile of the patients was mostly classified as ASA 2 and 3. There was the presence of at least one chronic disease in all patients with COVID-19 and in most patients without COVID-19. The mean BMI for patients with COVID-19 was type I obesity and overweight for the rest of the sample (p=0.043). There was a predominance of females among patients affected by COVID-19. Complications were longer postoperative hospital stay (p=0.015) and need for surgical approach (p=0.034). Conclusions: The profile of surgical patients with COVID-19 was linked to the presence of comorbidities, longer duration of the surgical procedure and high BMI. Complications associated with the presence of COVID-19 were longer postoperative hospital stays and surgical reoperation.